Kadar Ureum Sebelum dan Sesudah Hemodialisa pada Pasien Gagal Ginjal - Siti Kustiyah (Poltekkes Kemenkes Semarang, 2020)
Of chronic kidney failure is a state of decreased kidney function, where the kidneys are no longer able to excrete the rest of the body's metabolism. In end-stage chronic kidney failure hemodialysis is needed to eliminate the rest of the body's metabolism that accumulates in the blood and reduce the risk of death. The effectiveness of hemodialysis can be seen from the decrease in urea levels after hemodialysis. The purpose of this study was to determine the description of urea levels before and after hemodialysis in kidney failure patients. This research method uses descriptive observational data collection with URR (Urea Reduction Ratio) involving 130 patients with kidney failure who undergo hemodialysis. This research was conducted in July and October 2019 in the laboratory unit of the Klaten Islamic Hospital. The results There was a decrease in urea levels before and after hemodialysis. Where ureum levels before hemodialysis averaged 133.19 mg / dl and after hemodialysi s averaged 39.74 mg / dl . Conclusions Urea levels in patients with renal failure before hemodialysis increase / height can be 2 times or more than normal levels, an average of 133.19 mg / dl. Increased urea level increases influenced by several factors, including sex, age, indications such as supplements, medications and diabetes mellitus. Urea levels after hemodialysis average 39.74 mg / dl resulting in a decrease in urea levels before and after hemodialysis 70,16%.